Rooting of Stem Cuttings of Avicennia officinalis.Linn. And Avicennia alba BL. : a Tool for Afforestation of Blanks in Mangrove Forests - Kesava Reddy, K.; Venkaiah, K.; Bramaramba, B. (Indian Forester, 1994)
Mangroves are self maintaining estuarine components of the biosphere that are in continuous interaction with the terrestrial and marine-ecosystems. Vegetative propagation by rooting of stem cuttings of Avicennia species, one of the most important genera of the Godavari mangroves using root hormones IAA and IBA has been tried. The cuttings of Avicennia officinalis and Avicennia alba showed a good response in producing the roots with IBA 5000ppm followed by IBA 10000 ppm, IAA 5000 ppm and IAA 10000 ppm.